A nova produção independente: indústria fonográfica brasileira e novas tecnologias da informação e da comunicação - Marchi, Leonardo Gabriel de (2006)
In the present work, the object of study is the configuration of a independent phonographic production since the last years of 1990 s or, in other words, a New Independent Production. The hypothesis is that the emergency of these new brazilian record companies is related to the transformations in the local phonographic industry promoted by the new information and communication technologies and a New Economy of Information. In fact, the new tecno-economic regime based on the digital technologies along with the process of flexible production adopted by the majors companies had both allowed different phenomenons to happen in this industry s productive chain. One of them is the coming of the new independent companies which, taking advantage of the actual situation of the market, had become na important site of music production. Then, discussing the development of the brazilian phonographic industry and analizing two representative exemples of the NIP, the record companies Biscoito Fino and Trama, the roll of the independent prouction in the actual scenario of the local phonographic industry is subject o analysis.